Pengaruh Implementasi Kebijakan Beras untuk Rumah Tangga Miskin (Raskin) Terhadap Efektivitas Penanggulangan Kemiskinan (Studi Kasus Di Kecamatan Kendari Barat) - H. Muh. Amir (e-JKPP, 2015)
This research entitle the Policy Implementation program the Rice For The Family of Impecunious in Subdistrict of Kendari of West of Town Kendari. This Research study and know and also clarify the things which is concerning implementation of Rice policy For The Family of Impecunious.This research use the method of survai clarification explanatory survey method, in line with this research to analyse the influence usher the variable, that is Influence of Implementation of policy Rice Policy For The Family of Impecunious as free variable (independent variable) with the effectiveness of overcoming poorness in Subdistrict of Kendari West, as variable trussed (dependent variable). Researcher use the research approach in line with which wish reached by that is besides depicting and explaining fact empirik found in field, also will conduct the influence analysis usher the accurate variable.Pursuant to research result, that Implementation of Rice Policy For The Family of Impecunious in Subdistrict of Kendari West, uncommitted properly, so that its result not yet optimal, this matter is showingthat : ideal policy dimension, its execution not yet optimal because raskin still be imposed by a expense and society which there still not yet can buy, from dimension of policy target in this case society, not yet overcome by full of their requirement, because lowering nya mount the society ability, organizational dimension of executor, that implementor basically have run the the policy, but not yet ditunjukan seriousness in executing service to impecunious family. Environmental dimension of policy rice for the family of impecunious is not executed by according to operational standard, and also there no good coordination usher the sector, is so that happened by the difference of duty and authority usher the sectorConclusion that implementation of policy rice for the family of impecunious have an effect on the signifikan to effectiveness of overcoming poorness in Subdistrict of Kendari West. Contribution of Variable of Implementation of policy rice for the family of impecunious to